Acupuncture Attenuates Blood Pressure via Inducing the Expression of nNOS. (19th June 2021) - Wang, Lu; Yang, Na-Na; Shi, Guang-Xia; Wang, Li-Qiong; Li, Qian-Qian; Yang, Jing-Wen; Liu, Cun-Zhi
Abstract : Background . Sympathetic activation leads to elevated blood pressure. Neuronal nitric oxide synthase (nNOS) inhibits sympathetic nervous system activity, thereby decreasing blood pressure (BP). nNOS is highly expressed in the arcuate nucleus (ARC) and ventrolateral periaqueductal gray (vlPAG), which play essential roles in the regulation of the cardiovascular and sympathetic nervous systems. Objective . This study was designed to verify the hypothesis that acupuncture exerts an antihypertensive effect via increasing the expression of nNOS in ARC and vlPAG of spontaneously hypertensive (SHR) rats. Methods . Rats without anesthesia were subject to daily acupuncture for 2 weeks. BP was monitored by the tail-cuff method. nNOS expressions in the ARC and vlPAG were detected by western blot and immunofluorescence. BP was measured after 7-Nitroindazole (7-NI), a specific nNOS inhibitor, was microinjected into ARC or vlPAG in SHR rats treated with acupuncture. Results . Acupuncture for 14 days significantly attenuated BP, and the Taichong (LR3) acupoint was superior to Zusanli (ST36) and Fengchi (GB20) in lowering BP. In addition, acupuncture at Taichong (LR3) induced an increase of nNOS expression in ARC and vlPAG, whereas microinjection of 7-NI into ARC or vlPAG reversed the antihypertensive effect of acupuncture. Conclusions . This study indicates that acupuncture at Taichong (LR3) induces a better antihypertensive effect than at Zusanli (ST36) or at Fengchi (GB20) in SHR rats, and enhancement of nNOS in ARC and vlPAG probably contributes to the antihypertensive effect of acupuncture.